The prevalence of chronic kidney disease and associated factors among adult patients with type 2 Diabetes Mellitus who attend the diabetes centre in Gaborone, Botswana - Radikara, N. (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2017.